Kajian Kebutuhan Pasca Bencana (Bidang Rehabilitasi Dan Rekonstruksi) Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Kutai Kartanegara (Kajian Di Desa Tuana Tuha Kenohan) - Akbar, Ali; Sundoyo, Sundoyo (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
This research was conducted through a Post Disaster Needs Assessment (PDNA) which included assessing the consequences of disasters, disaster impacts, and post-disaster recovery needs. The research method used in this study is descriptive analysis with a quantitative approach, which aims to explain a phenomenon that uses numbers and describes the characteristics of the subject being studied or researched so as to get a picture of a certain event. Damage to infrastructure that occurred in the disaster located in Tuana Tuha Village, Kenohan District due to erosion caused physical losses to the land transportation sub-sector, water resources sub-sector, clean water and lighting sub-sector. Given the damage to roads and bridges that connect several sub-districts in the Sungai Belayan area in Kuti Kartanegara Regency, it has an impact on economic, educational, social, cultural and other aspects, from the results of this study, it is appropriate for the Government to pay attention and accommodate proposals in the form of funds. , procurement of materials or repairs, relocation areas and other relevant recommendations from the results of the post-disaster Needs study that occurred in the Keliran hamlet, Tuana Tuha Village, Kenohan sub-district which was affected by the disaster.